Mahurui Hatulang Kabalim Traditional Mediation (A Household Dispute Resolution in Central Katingan, Central Kalimantan) - Pelu, Ibnu Elmi Acmad Slamat; Hasan, Ahmadi; Sadiani, Sadiani; Patrajaya, Rafik; Fajrianor, Haris; Tarantang, Jefry (Kertha Patrika, 2022)
This study examined a traditional mediation of mahurui hatulang kabalim which is a local wisdom of indigenous Dayak society in Central Katingan, Central Kalimantan who has a traditional mentality and belief in resolving household disputes. Mahurui hatulang kabalim is rooted on conciliation and deliberation culture as society values transforming into the character which is manifested into mechanical solidarity. This study was an empirical legal study or so-called non-doctrinal sociological legal study. The approaches applied in this study were explanatoris approach, conceptual approach and philosophical approach. In the mediation practice of Mahurui hatulang kabalim, the mantir adat as a mediator to resolve disputes was by  mangatawan masalah (knowing the problem), nyundau ije-ije (visiting respectively), ngahau ije-ije (calling respectively), Manggau jalan damai (seeking a peaceful way), manukep atei (approaching the heart). Some were successfully reconciled (sarukui haluli) and some were failed to reconcile (separate pinja). The essence of Mahurui hatulang kabalim was a traditional mediation as a repressive effort in restoring family relations as society’s traditional mentality.